Impact and nature of Total Quality Management practices on performance of and employee effectiveness as an important variable (Czech Journal of Multidisciplinary Innovations, 2026)
We must emphasize the importance of monitoring the dimensions of Total Quality Management (TQM) (Reliability (RE), Performance (PE), and Empathy (EM)) according to specific and clear considerations that benefit projects within the Babylon Chamber of Commerce (BCC). Quality in projects is indispensable and cannot be overlooked, as it is the primary factor in stability. Our research was meticulous, leaving no detail unexamined. The researcher was aware of the unique technical and beneficial nature of his work. The researcher began working with )116 ( employees at the Babylon Chamber of Commerce, collecting )110 ( data points, while )6 ( were incomplete. SPSS was primarily used to analyze the results. The three hypotheses were successfully tested.